Gestational diabetes mellitus and children's social-emotional development, behavioral problems, and psychological adjustment - Mattila, Inka; Nolvi, Saara; Kataja, Eeva-Leena; Tuulari, Jetro J.; Korja, Riikka; Scheinin, Noora M.; Kaaja, Risto; Karlsson, Hasse; Ekholm, Eeva; Karlsson, Linnea (Springer Nature, 2025)
Background This longitudinal cohort study investigated whether gestational diabetes mellitus (GDM) is associated with 2- and 5-year-old children's social-emotional development and whether child sex moderates the association.
Methods FinnBrain Birth Cohort Study recruited 3808 pregnant women 2011-2015 in Finnish Turku region and & Aring;land Islands. Their children's social-emotional development at 2 years was measured by Brief Infant Toddler Social Emotional Assessment (BITSEA) (N = 1444, GDM n = 227) and at 5 years by Strengths and Difficulties Questionnaire (SDQ) (N = 1489, GDM n = 225). General linear models were used.
Results After adjusting for covariates, GDM was not associated with children's social-emotional development at age 2 years. At age 5, GDM was associated with greater total behavioral difficulties (p = 0.025, for 1-point increase in total score eta 2 = 0.004). Sex-stratified analyses showed GDM was associated with greater internalizing problems in girls at 2 years (p = 0.044, eta 2 = 0.007), and greater conduct problems (p = 0.018, eta 2 = 0.007), hyperactivity/inattention (p = 0.001, eta 2 = 0.014) and total difficulties (p < 0.001, eta(2) = 0.015) in boys at 5 years. Interaction of child's sex and GDM was observed for hyperactivity/inattention (p = 0.015) and total difficulties (p = 0.019) at 5 years.
Conclusion GDM may influence children's social-emotional development, behavioral problems, and adjustment-and, furthermore, in a sexually dimorphic manner. Longer follow-up is needed to evaluate long-term stability of findings. Impact Gestational diabetes mellitus (GDM) was associated with greater total behavioral difficulties of offspring at the age of five. GDM was associated with greater internalizing problems in girls at 2 yearsGDM was associated with greater conduct problems, hyperactivity/inattention and total difficulties in boys at 5 years.GDM may influence children's social-emotional development in a sexually dimorphic manner.Findings call for further study of mechanisms of children's social-emotional development as well as shed light on GDM-related risk factors for early intervention.